Analisis Kualitas Kinerja Pegawai Dinas Sosial Provinsi Sumatera Utara Bidang Program, Akuntabilitas Dan Informasi Publik Dalam Sistem Penyelenggaraan Pelayanan Publik - Dedy Damhuri; Kusmilawaty Kusmilawaty (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The aim of this research is: To determine the quality of performance of North Sumatra Province Social Service Employees, especially in the Program, Accountability and Public Information Sectors in the Public Service Delivery System. This study uses a qualitative method. Data collection was carried out through observation, interviews and documentation. The informants in this research were 4 people, namely the Secretary of the North Sumatra Province Social Service, Head of the Program, Accountability and Public Information Section, Program, Accountability and Public Information Officer, and Honorary Employees. The results of the research show that the quality of performance of North Sumatra Province Social Service employees in the areas of Programs, Accountability and Public Information is running well in accordance with employee performance. Based on interviews with informants, employees in the Program, Accountability and Public Information Division also have the same opinion regarding personal potential, optimal work results, work processes and enthusiasm at work. Therefore, it can be suggested that in the future, if you want to recruit new employees, pay more attention to the field of science or major according to the abilities of the prospective new employee so as to facilitate all better work processes in the Program, Accountability and Public Information fields.